STUDI KEANEKARAGAMAN JENIS KUPU-KUPU DI DAS MENDALAM TAMAN NASIONAL BETUNG KERIHUN DANAU SENTARUM KABUPATEN KAPUAS HULU PROVINSI KALIMANTAN BARAT - Rinanda, Aris; Diba, Farah; Wahdina, . (Universitas Tanjungpura, 2016)
Betung Kerihun-Danau Sentarum National Park in Kapuas Hulu District has a highest biodiversity on plant, animal and insect. One of the interesting insect is butterfly. Butterfly has an important function for indicator of the health of environment. The purpose of research is to identify the butterfly in DAS Mendalam region in Betung Kerihun-Danau Sentarum National Park. The location of research was in Mentibat river and Pari river. Methodology of research used exploration method which combined with transects method. Area of research consists of aquatic and terrestrial. The length of transect was 1 Km with observation area 5 m both on left and right side. Exploration the biodiversity of butterfly was conducted in the morning from 06.00-09.00 wib and in the afternoon from 15.00-17.00 wib. Result of the research showed that 22 species of butterfly was found, consist of 4 families and total individual was 298 butterflies. The families consist of Lycanidae, Nymphalidae, Papilionidae, and Pieridae. Mentibat River has a highest diversity of butterfly than Pari River. 16 species was found in Mentibat River, consist of Jamides pura, Charaxea affinia, Euplea rhadamanthus, Euripus nyctelius, Idea stolli, Polyura athatmas, Graphium arycles, Graphium doson, Graphium antiphates, Papilio memnon, Trogonoptera brookiana, Troides amphtysus, Appias lycinida, Eurema hecabe, Hebomia glaucipe, Ixias undatus. Total individual found was 200 butterflies. The value of Dominance Index was 0.10; Diversity Index was 1.09; Abundance Index was 180.55; Species Richness Index was 6.52 and Similarity Index was 0.42. Meanwhile in Pari River was found 14 species of butterflies consist of Jamides pura, Chersonesia rahria, Cupha erymanthis, Moduza procris, Polyura athatmas, Graphium sarpedon, Graphium antiphates, Papilio memnon, Appias lycinida, Eurema hecabe, Eurema sari, Hebomia glaucipe, Ixias undatus, and Pareronta valeria. The value of Dominance Index was 0.09; Diversity Index was 1.09; Abundance Index was 93.21; Species Richness Index was 6.53 and Similarity Index was 0.42 and the total individual found was 98 butterflies. The environment in Betung Kerihun-Danau Sentarum National Park was convenient to butterfly. The result of research givinginformation about the biodiversity of butterfly in Betung Kerihun-Danau Sentarum National Park for the conservation management in this area. Keywords: Betung Kerihun Danau Sentarum National Park, biodiversity, butterfly, Lycanidae, Nymphalidae, Papilionidae, Pieridae